PERILAKU BELAJAR MAHASISWA PROGRAM STUDI S1 AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA - Yunita, Anne; Ludigdo, Ak., CA, Prof. Dr. Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this study is to know about student learning behavior patterns in accounting bachelor’s degree of Economics and Business Faculty, Brawijaya University. The informants in this study amounted to 6 students who are grouped to Grade Point Average (GPA) below 3,0; between 3,0 to 3,5; and also more than 3,5. The data that used are the primary data, retrieved by using interview method. The type of this research is a descriptive research which is try to discover the learning behavior’s phenomenon of three student types that are study oriented, hedonic, and activists. The result of this study indicate that basically the student behavior is extremely diverse. So, the grouping of students cannot always be identical with a high or low Grade Point Average (GPA). Beside that, the grouping of students also cannot always be identified with their learning behavior patterns. Keywords: behavioral learning, grouping of students, accounting bachelor’s degree